Smooth elastic contact of cylinders by caustics: the contact length in the Brazilian disc test (Archives of Mechanics - Test, 2013)
The smooth contact of two elastic cylinders compressed against each other along a common generatrix is studied analytically and experimentally. The main objective is the quantification of the length of the contact arc. For the analytic study, the complex potentials method is employed while experimentally the contact arc’s length is determined by extending the reflected caustics technique. A series of experiments are then carried out using the device suggested by the International Society for Rock Mechanics for the standardized implementation of the Brazilian test and the typical set-up of the reflected caustics method. The experimental results are compared to the analytically determined ones. The agreement is satisfactory especially for low load levels, ensuring validity of the linear elasticity assumption.